Fetal assessment after Zika exposure. - Papageorghiou, A (Wiley, 2016)
The papers, commentaries and debates in this issue of the journal highlight a number of uncertainties regarding Zika Virus in pregnancy. About 80% of Zika virus infections inadults occur without distinguishing symptoms. Whether this is true for pregnant women remains unknown as is any relationship between the presence or absence of specific symptoms and the risk of maternal to fetal viral transmission. The CDC documented (Armstrong et al (Morbidity and Mortality Weekly Report (MMWR), March 18, 2016) that all 115 adult USA residents with laboratory evidence of recent Zika virus infection reported a clinical illness. Whether symptomatic disease is indeed as common as initially thought is important, but in the meantime it seems prudent to monitor at risk exposed pregnant women. Although Zika serology remains imperfect and crossreactivity with other filiviruses is a problem, a negative result should provide a degree of reassurance.